Nicotine supplementation does not influence performance of a 1h cycling time-trial in trained males - Mündel, T.; Houltham, S. D.; Barnes, M. J.; Stannard, S. R. (Frontiers in Physiology, 2019)
The use of nicotine amongst professional and elite athletes is high, with anecdotal evidence indicating increased prevalence amongst cycling sports. However, previous investigations into its effects on performance have not used high-validity or -reliability protocols nor trained cyclists. Therefore, the present study determined whether nicotine administration proved ergogenic during a ~1 h self-paced cycling time-trial (TT). Ten well-trained male cyclists (34 ± 9 years; 71 ± 8 kg; www.frontiersin.orgO2max: 71 ± 6 ml · kg-1 · min-1) completed three work-dependent TT following ~30 min administration of 2 mg nicotine gum (GUM), ~10 h administration of 7 mg · 24 h-1 nicotine patch (PAT) or color- and flavor-matched placebos (PLA) in a randomized, crossover, and double blind design. Measures of nicotine`s primary metabolite (cotinine), core body temperature, heart rate, blood biochemistry (pH, HCO3-, La-) and Borg`s rating of perceived exertion (RPE) accompanied performance measures of time and power output. Plasma concentrations of cotinine were highest for PAT, followed by GUM, then PLA, respectively (p < 0.01). GUM and PAT resulted in no significant improvement in performance time compared to PLA (62.9 ± 4.1 min, 62.6 ± 4.5 min, and 63.3 ± 4.1 min, respectively; p = 0.73), with mean power outputs of 264 ± 31, 265 ± 32, and 263 ± 33 W, respectively (p = 0.74). Core body temperature was similar between trials (p = 0.33) whilst HR averaged 170 ± 10, 170 ± 11, and 171 ± 11 beats · min-1 (p = 0.60) for GUM, PAT, and PLA, respectively. There were no differences between trials for any blood biochemistry (all p > 0.46) or RPE with mean values of 16.7 ± 0.9, 16.8 ± 0.7, and 16.8 ± 0.8 (p = 0.89) for GUM, PAT, and PLA, respectively. In conclusion: (i) nicotine administration, whether via gum or transdermal patch, did not exert an ergogenic or ergolytic effect on self-paced cycling performance of ~1 h; (ii) systemic delivery of nicotine was greatest when using a transdermal patch; and (iii) nicotine administration did not alter any of the psycho-physiological measures observed.